Using water adsorption measurements to access the chemistry of defects in the metal–organic framework UiO-66. Issue 29 (2nd March 2017) - Dissegna, Stefano; Hardian, Rifan; Epp, Konstantin; Kieslich, Gregor; Coulet, Marie-Vanessa; Llewellyn, Philip; Fischer, Roland A.
Abstract : Defects in UiO-66 were investigated for the first time by water adsorption measurements and then the materials were tested for the cyanosilylation of benzaldehyde. Abstract : Tailoring defects in metal–organic frameworks is important for enhancing sorption and reaction properties. Defects in UiO-66 have been characterized for the first time by using water adsorption measurements. We found that the defect-induced hydrophilicity, quantitatively expressed by the Henry constant and the saturation water uptake, correlates well with the catalytic performance in the cyanosilylation of benzaldehyde.